The Right to City: How Location Change Decisions Influence Peoples Rights on Cities via Sample of Üçkuyular Market - Gelişkan, Nil Nadire (ICONARCH International Congress of Architecture and Planning, 2017)
Market places are important nodes of the cities which take places on definite days of the week. Especially in Izmir you can find a market on any day of the week at any region. For instance there are on Wednesdays Bostanlı market, on Saturdays Özkanlar market, on Tuesdays Hatay market etc. Üçkuyular market is one of the popular market place of Izmir which takes place every Sunday and becomes specialized with fresh fruits and vegetables selling including other fields (clothing, charcuterie, fish market). Strategically markets establish at reachable points with both vehicle and foot. Üçkuyular as a region serves transfer center for metro, bus, ferry, dolmush for districts and tram in the near future. However with sudden decision of authorities location of Üçkuyular market moved from its place to under viaducts of highway. In this paper, it is aimed to examine how these kinds of decisions were taken free from users with ignoring “right to the city”. Right to the city as a concept introduced by Lefebvre as “…the right information, the rights to use of multiple services, the right of users to make known their ideas on the space and time of their activities in urban areas; it would also cover the right to the use of the center”.* In addition to that old market place and expected one will be examined through Rem Koolhaas’s junkspace definition which is “The built product of modernization is not modern architecture but Junkspace. ” **